Svensk folkehøjskole og Grundtvig - Nielsen, Valdemar (Grundtvig-Studier, 1961)
The Swedish Folk High-School and Grundtvig. By Valdemar Nielsen When the first Swedish Folk High-School began their activities in 1868 it was 24 years after the setting up of the first Danish High-School in Rødding and four years after the setting up of the first Norwegian High-School in Hamar. until the years immediately preceding this event, very little had been known about these schools in Sweden. It was interest in the idea of a more advanced type of education than could be given by the primary school – an interest which naturally made itself evident after the passing of new legislation concerning localgovernment in 1862 and new arrangements for Parliamentary representation in 1866 - that first directed attention to the neighbouring country’s new schools for young adults. At that time Denmark had about 20 Folk High-Schools, and it was especially towards these that attention was directed; information about them was sought in order that they might be taken as a model for the establishment of semilar schools in Sweden. And in this process people in Sweden also learned that it was the clergyman, poet, historian and author, N. F. S. Grundtvig, who had set forth the idea of these schools and called for their establishment in a series of writings. At first it was chiefly the organisation and methods of working of these schools which attracted interest in Sweden, and not so much Grundtvig’s views about them and the idea which lay behind them. None of the men who took up the work in Sweden entered into personal contact with Grundtvig or had any knowledge of his writings about the new type of school when they began their work. Especially those men who took up the work in Denmark after 1864 were strongly influenced by Grundtvig, and therefore the Folk High-Schools there came to be generally described as “Grundtvigian.” Like everything new, they were objects for a good deal of criticism from different quarters, and this criticism also found its way to Sweden and was directed against the new schools there, so that their leaders found it necessary to stress the point that they were not in any way Grundtvigian. They thought, too, that a type of school somewhat different from the Danish one would be necessary in Sweden, if the new schools were to win the confidence of the people and attract students. A certain caution —not to say suspicion—in the attitude of the Swedish Folk High-School men was therefore prevalent for a number of years. They wanted, in fact, to find their own type of education and get it established first, before entering into closer relations with the Danes. This only came about after 1880, and in 1883, the hundredth anniversary of Grundtvig’s birth, they met for the first time at a Scandinavian Folk High-School Meeting. This took place at Testrup High-School near Aarhus in Jutland, and there was general satisfaction about the contacts which were thus created. The most prominent man in the Danish Folk High-School movement, Ludvig Schrøder, Headmaster of Askov, wrote about this afterwards: “It was most especially making acquaintance with our fellow-workers in Sweden, who had previously been unknown to nearly all the Danes and Norwegians, that gave this meeting its great significance”, and Leonard Holmström, Headmaster of Hvilan, whose position among his Swedish colleagues was like that held by Schrøder in Denmark, after mentioning the gulf which had hitherto existed between them, declared, “But then came the visit of the Norwegian and the Swedes to Denmark, and only then they became clear as to what the Danish Folk High-School aimed and what a powerful and beneficial influence it had already exerted on the life of the people. They saw its seeds growing up in real life and became convinced that, far from having vague dream-pictures as their fruits among the students, these seeds bore fruit in the form of work in Christian confidence and love among both men and women.” During the meeting they had also come to know a little more about Grundtvig and his significance for the Folk High-School, and when the Norwegian and Swedish guests visited the south of Jutland after the meeting was over, and at Skamlingsbanken heard about the speech there in which Grundtvig had welcomed Rødding High-School in 1844 as the first realisation of his idea, Dr. Holmström of Hvilan conceived the idea that a memorial should be set up to Grundtvig on the hill, and that members of the Norwegian and Swedish High-School movements should do this. In the following year the memorial was unveiled with a speech by Dr. Holmström, who paid tribute to Grundtvig as the originator of the Folk High-School and referred to the way in which this idea from Denmark had spread to the other Scandinavian countries and had become a link of great value between the Scandinavian nations. Already in 1881 another prominent Swedish High-School, teacher, Teodor Holmberg, Headmaster of Tärma Folk High-School, had written in an article in “Pædagogisk Tidskrift” (“Educational Periodical” ): “Grundtvigs name is inseparably connected with the Folk High-School movement. He is the father of the Folk High-School. It is almost imposible to realise how deeply his influence has penetrated into the life of the Danish people through his new contribution in the sphere of education . . . For a very long time nobody has had such an influence as he on the life of his people, and, indeed, on the life of all the people of Scandinavia.” Dr. Holmström wrote about the Scandinavian Folk High-School in “Nordisk Tidskrift” (“Scandinavian Magazine” ) in 1886, and said, among other things: “as a result of the influence from Denmark there was an increased desire to contribute to the spiritual development of the students with all the means which are available to the teacher. From the Danes the Swedish teachers learnt to live with the students in a free, straigtforward and friendly fashion, to use the spoken word in their teaching in a way that was simple and true to the life of the people (“folkeligt” ), and to awaken the interest of the students in their own fatherland.” Since 1883 a long series of Scandinavian High-School Meetings has been held in the different Scandinavian countries, at which those present have exchanged ideas about their work and experiences and the difficulties connected therewith. At these, different views have usually been expressed, not least with regard to the “living word” so strongly emphasised by Grundtvig. As a result of his experiences as a student in the “Latin school” of his day, where the chief emphasis was on formal education, Grundtvig wanted the new school to have an awakeneing influence to a very different extent, by appealing to the feelings of the students and nourishing their imagination. Books should have a less important place in the teaching, which should be imparted mainly through the spoken word in lecture and discussion. On the Swedish side people did not fully understand the significance and value of this; and in particular, they did not think that it would be suitable for Sweden, where it was assumed that the students were better fited for working independently with books. And therefore on the Danish side people sometimes felt that the schools they had in Sweden were not real High-Schools, but rather some kind of technical schools (“realskoler”). On the other hand people in Sweden thought that the students in the Danish High-Schools did not learn anything. The discussion of this question could sometimes become rather sharp, as at a Scandinavian Meeting in 1921, when a Swedish High-School Headmaster, took the opportunity of saying: “The Danish school lives according to its ideas, but we Swedes must be allowed to go our own way. We are not identical, and thank God for that! But it is important that we shall respect each other’s separate individuality” Sometimes, however, members of the Swedish High-School movement are apt to feel as if their schools lacked some of the characteristics that make them Folk High-Schools. In 1937 “Tidskrift för svenska folkhögskolan” (“Swedish High-School Magazine” ) published an article with the title “Tilbaka till Grundtvig” (“Back to Grundtvig” ). It was written by a High-School teacher who thought that in the effort to impart knowledge which was characteristic of the Swedish Folk-High-School there was still something of the nature of the “black school” against which Grundtvig had expressed himself so strongly, and that it might therefore be appropriate to use the “living word” in its good sense, to a somewhat greater extent. Others, too, have spoken of the importance of “going to school with Grundtvig again,” and in 1945 a Swedish High-School teacher wrote of the valuable inheritance which the Swedish High-School, too, has received from Grundtvig and the significance which it still has. The veteran Headmaster of Bruunsviks Folk High-School in Dalarne, Alf Ahlberg, Ph. D., in 1943 stressed another side of the inheritance received from Grundtvig, namely the conception of man as a whole, as a being with both body and spirit, which was also the foundation for his conception of the High-School, and which it is more necessary to emphasize in our time than ever before, perhaps, in face of the belittling of the human personality which we have experienced. In an account of the position and tasks of the Folk High-School which was published by a Swedish Educational Commission in 1953, these words occur: “Grundtvig’s original Folk High-School programme has always been of significance for the Swedish Folk High-School even if the religious tendency which found his leader in him—a tendency which has meant much for the formation and development of the Danish Folk High-School—did not have any noticeable significance in Sweden, either for the Folk High-School or for the rest of the country.” Here, in an official document, Grundtvig’s significance for the Swedish Folk High-Schools is recognised. How extensive this significance has been in the life and work of the individual schools is difficult to establish, but that it has existed there can be seen when visiting Folk High-Schools and when reading their annual reports and the publications celebrating their jubilees.